2019
DOI: 10.1016/s1474-4422(19)30034-1
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of stroke, 1990–2016: a systematic analysis for the Global Burden of Disease Study 2016

Abstract: Summary Background Stroke is a leading cause of mortality and disability worldwide and the economic costs of treatment and post-stroke care are substantial. The Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) provides a systematic, comparable method of quantifying health loss by disease, age, sex, year, and location to provide information to health systems and policy makers on more than 300 causes of disease and injury, including stroke. The results presented here ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
950
2
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,142 publications
(998 citation statements)
references
References 33 publications
7
950
2
12
Order By: Relevance
“…Failing to replicate the instrumental variable estimates Millwood et al 2019 found among participants in the China Kadoorie Biobank sample supports the hypothesized differential effect of alcohol consumption on CVD risk across ethnic backgrounds 14,39 . East Asia has the highest prevalence of stroke worldwide 40 , and generally lower alcohol consumption behaviors than European countrie. 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Failing to replicate the instrumental variable estimates Millwood et al 2019 found among participants in the China Kadoorie Biobank sample supports the hypothesized differential effect of alcohol consumption on CVD risk across ethnic backgrounds 14,39 . East Asia has the highest prevalence of stroke worldwide 40 , and generally lower alcohol consumption behaviors than European countrie. 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a leading cause of death and disability worldwide (1). According to the most recent report from the Global Burden of Disease Stroke Collaboration, there were 1·03 million incident strokes in Western Europe and 0·81 in North America in 2016 (1).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a leading cause of death and disability worldwide (1). According to the most recent report from the Global Burden of Disease Stroke Collaboration, there were 1·03 million incident strokes in Western Europe and 0·81 in North America in 2016 (1). Despite a substantial decline in stroke mortality in recent decades, stroke is the second leading cause of cardiovascular death worldwide (2).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a leading cause of death worldwide and the leading cause of permanent disability 1,2 . About 80% of stroke cases are of ischaemic origin 3 . The risk of ischaemic stroke is determined by a complex interplay of genetic and environmental factors partly acting through modifiable risk factors such as hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%